Strategi Pemasaran Pasca Pandemi Pada Lembaga Pendidikan Prima Mandiri Utama - Fendy Hariatama; Alexandro, Rinto; Liling Lenlioni; Jesika Widiasari Sitepu; Josepin Agustina Siahaan (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
This article discusses post-pandemic marketing strategies that can be implemented by the Prima Mandiri Utama Education Institute to face new challenges and opportunities in the world of education. Taking into account changes in consumer behavior patterns and post-pandemic market dynamics, this research explores various innovative approaches in education marketing with the aim of obtaining data on the marketing strategies of the main prima mandiri educational institutions post-pandemic. The method used is a qualitative research method that involves collecting and analyzing data in the form of text, images, or sounds. This method emphasizes interpretation, theory development, and understanding of the context in which the marketing strategy is carried out. The overall analysis shows that Prima Mandiri Utama Educational Institution has a main focus on improving the quality of teaching and services as an effort to form quality human resources (HR), with students as the main customers. Post-pandemic, the institution's marketing strategy has undergone significant changes, promoting through competitions, socialization, and social media, especially Instagram. post-pandemic marketing strategy focuses more on utilizing digital marketing, while still conducting direct marketing through competitions and educational-themed seminars.